Green marketing strategies in the dairy sector: Consumer‐stated preferences for carbon footprint labels1. (2nd July 2019) - Canavari, Maurizio; Coderoni, Silvia
Abstract: Italian consumers' serveyed revealed a generally positive willingness to pay for milk labeled for lower carbon footprint. Green marketing and related sustainable labels are important devices to convey information to consumers about more sustainable business models. Italian consumers' willingness to pay for milk with lower carbon footprint analyzed through a pilot survey is positive and significant. Consumers' willingness to pay also depends on the importance consumers assign to climate change, price sensitivity, as well as on income.